Changes in the Microbiome in Cirrhosis and Relationship to Complications: Hepatic Encephalopathy, Spontaneous Bacterial Peritonitis, and Sepsis - Lachar, Jatinder; Bajaj, Jasmohan S. (Seminars in Liver Disease, 2016)
Chronic liver disease with progression to decompensated cirrhosis and its associated complications, including hepatic encephalopathy, spontaneous bacterial peritonitis, and sepsis, is a leading cause of mortality and morbidity. The pathophysiology of decompensated cirrhosis, which is being intensively studied, leads to the development of gut microbiome changes causing dysbiosis. This is likely related to altered bile acid composition, with a subsequent increase in the relative abundance of potentially pathogenic bacteria that contributes to hepatic encephalopathy and leads to their translocation and the development of spontaneous bacterial peritonitis and bacteremia. Treatments for these conditions have been found to target the gut microbiome, which has become a vital area of study in the treatment of cirrhosis.
Keywords: hepatic encephalopathy; rifaximin; lactulose; infection; cirrhosis dysbiosis ratio